2006
DOI: 10.1577/h05-047.1
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Myxobolus cerebralis Resistance among F1‐Generation Crosses of Whirling Disease Resistant and Susceptible Rainbow Trout Strains

Abstract: A whirling disease resistant domestic strain of rainbow trout Oncorhynchus mykiss (German [GR]) was crossed with a susceptible wild strain of rainbow trout (Colorado River [CR]). Thirty-two families of F 1 crosses, along with five pure GR and two pure CR rainbow trout families, were then evaluated for resistance to whirling disease after experimental exposure to Myxobolus cerebralis. The pure domesticated GR strain was verified to have strong resistance to the parasite. In contrast, wild CR rainbow trout were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(76 citation statements)
references
References 20 publications
7
66
2
Order By: Relevance
“…Fish were then exposed to triactinomyxons, the waterborne infectious stages of M. cerebralis, at a dose of 1000 triactinomyxons per individual for 1 h at 15 1C (Schisler et al, 2006). The fish were held in aquaria receiving 15 1C well water with a daily ration of commercial trout diet for 60 days after pathogen exposure (1251-1324 degree days).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish were then exposed to triactinomyxons, the waterborne infectious stages of M. cerebralis, at a dose of 1000 triactinomyxons per individual for 1 h at 15 1C (Schisler et al, 2006). The fish were held in aquaria receiving 15 1C well water with a daily ration of commercial trout diet for 60 days after pathogen exposure (1251-1324 degree days).…”
Section: Methodsmentioning
confidence: 99%
“…Although a few native US strains have begun to demonstrate modest levels of whirling disease resistance (Wagner et al, 2006), Hofer is currently the only known strain to display resistance at both consistent and high levels across individuals. Controlled experimental studies comparing Hofer and susceptible laboratory strains of O. mykiss, along with their crossed progeny, have revealed that whirling disease resistance has a genetic component (Schisler et al, 2006). To date, genetic studies of the O. mykiss whirling disease phenotype have primarily focused on candidate (Severin and El-Matbouli, 2007) and global (Baerwald et al, 2008) gene expression changes in response to infection.…”
Section: Introductionmentioning
confidence: 99%
“…El-Matbouli et al (2002) found that, under experimental laboratory conditions, a German strain of rainbow trout (German Rainbow, GR) was at least as resistant to M. cerebralis as brown trout Salmo trutta, which evolved with the parasite in its European home range (Hoffman 1970). The GR strain was also found to be more resistant to M. cerebralis than either the North American Trout Lodge (TL) or Colorado River Rainbow (CRR) trout strains (Hedrick et al 2003, Schisler et al 2006. Resistance likely arose through the growth and reproduction of the GR strain under continuous exposure to the parasite in Bavarian hatcheries (Hedrick et al 2003).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…The CRR strain is susceptible to infection by Myxobolus cerebralis and has experienced severe population declines in areas where the disease has been introduced (Nehring & Thompson 2001). Resistant GR fish were crossed with susceptible CRR fish to incorporate whirling disease resistance from the GR strain into a population that retained many of the desired characteristics influencing the ability to survive and reproduce in the wild, which may have been lost in the highly domesticated GR strain (Schisler et al 2006). Besides being domesticated, the GR strain is inbred and exhibits low heterozygosity (El-Matbouli et al 2006), which may compromise its survival and adaptation in natural environments.…”
Section: Brood Stock Developmentmentioning
confidence: 99%
“…The exploitation of the immune system through breeding selection programmes is a promising future strategy to control myxosporoses, but much work is still to be done concerning the selection of resistant strains, as in most cases the genetic base is unknown. For C. shasta, multiple gene loci have been found associated to resistance in O. mykiss (Nichols et al, 2003), for M. cerebralis, inheritance of resistance in disease resistant rainbow has been shown (Schisler et al, 2006), and for PGD a genetic component for resistance in catfish has been suggested (Bosworth et al, 2003). …”
Section: Future Research Perspectivesmentioning
confidence: 99%